Nutritive value of Mulato grass under di erent grazing strategies - Cruz-Hernández, Aldenamar; Hernández-Garay, Alfonso; Aranda-Ibáñez, Emilio Manuel; Chay-Canul, Alfonso J.; Márquez-Quiroz, César; Rojas-García, Adelaido R.; Gomez-Vázquez, Armando (Ecosistemas y Recursos Agropecuarios, 2016)
The objective of this study was to evaluate the e ect of grazing frequencies and intensities on herbage accumulation and nutritive value of Brachiaria hybrid 36061 cv. Mulato. Grazing frequencies of 14, 21 and 28 d and intensities of 9 to 11 and 13 to 15 cm were studied under a randomized block design in a 3x2 factorial arrangement with three replicates. Herbage accumulation, morphological components, in situ digestibility (DIGDM), crude protein (CP), neutral detergent ber (NDF) and acid detergent ber (ADF) were evaluated. Annual yield distribution was 55, 28 and 16 % during the rainy, northern cold-front and dry seasons, in the rst cycle, with the highest annual accumulation of 12 310 kg DM ha−1 obtained by grazing every 28 d. The highest DIGDM and PC were obtained by grazing at an intensity of 9 to 11 cm every 14 d in all seasons. However, grazing at an intensity of 13 to 15 cm every 28 d resulted in greater forage yield with a high concentration of NDF and ADF. In conclusion, the greatest herbage accumulation, NDF and ADF were recorded by grazing of 13 to 15 cm in height every 28 d in both cycles. DIGDM and CP had high values by grazing of 9 to 11 cm every 14 d.